Synthesis of Hydrogels by Free Radical Copolymerization of Sago Starch or Chitosan and Hydrophilic Vinyl Monomers and Their Characterizations - Najjar, Abduel Majid K. (2002)
Sago starch was incorporated in the synthesis of polymer gel networks by free radical crosslinking copolymerization in an aqueous solution using potassium persulfate as an initiator. Three different monomers (2-acrylamido-2- methylpropanesulfonic acid (AMPS), acrylic acid and methyl-2-acrylamido-2- methoxyacetate (MAMOA)) with a common crosslinking agent (N,N'- methylenebisacrylamide (NMBA)) were used to synthesize these gel networks. A series of studies was carried out to evaluate and optimize the effect of the reaction parameters such as the amount of the monomer, the cross linking agent and sago starch as well as liquor volume on the polymer gel networks yield. It was found that the percentages of gelation fraction and total conversion were dependent on these parameters. The swelling behaviors of these polymeric gel networks from the dry state In distilled water and NaCl solutions of different concentration were also investigated. The maximum saturated water absorbency of 440 g H₂O/g dry gel was obtained for the gel network prepared from 1 g sago starch, 38.16 x l0⁻³ mol AMPS and 1.29 x l0⁻³ mol NMBA in the presence of 45 mL liquor volume. The absorbency of the hydrogel networks in the salt solutions was affected by the salt concentrations and the charge number of cations and anions.